LB0003 A Randomized Controlled Study of Laquinimod in Active Lupus Nephritis Patients in Combination with Standard of Care. (23rd January 2014) - Jayne, D.; Appel, G.; Chan, T. M.; Barkay, H.; Weiss, R.; Wofsy, D.
Abstract : Background: Laquinimod (LAQ) is a novel oral immunomodulator in development for the treatment of Lupus Nephritis (LN). LAQ has an immune modulatory effect on antigen presenting cells directing T cells towards an anti-inflammatory phenotype characterized by down regulation of proinflammatory cytokines, including IL-6, IL-12, IL-17, IL-23, and TNFa, and increased production of IL-10. Objectives: To evaluate the safety, tolerability & clinical effect of LAQ vs. placebo in patients with active LN receiving standard of care (SoC; i.e . mycophenolate mofetil (MMF) and corticosteroids). Methods: Phase IIa, multicenter, double-blind, randomized study to evaluate the safety, tolerability and clinical effect (including changes in eGFR & proteinuria) of LAQ in combination with SoC. 46 patients with active LN were randomized to 24 weeks of treatment with LAQ 0.5mg/day (n=16), LAQ 1mg/day (n=15), or placebo (n=15). Results: The percentage change from baseline in eGFR at week 24 was greater in both LAQ groups vs. placebo (0.5mg vs. 1mg LAQ vs. placebo: 18.0 ± 30.7 vs. 24.3 ± 28.8 vs. 12.1 ± 20.2, respectively). The percent change from baseline in spot urine protein: creatinine ratio also showed a difference between treatment arms in favor of LAQ (0.5mg vs. 1mg LAQ vs. placebo: -61.4 ± 22.8 vs. -23.0 ± 53.6 vs. -8.3 ± 81.26, respectively). Renal responses were greater at week 24 with LAQ vs. placebo (ALMS study criteria – based on spot urine instead of 24hr collection): In the LAQ 0.5mg group, 10 patients (62.5%) achieved renal response compared to 6 (40%) in the LAQ 1mg group and 5 (33.3%) in the placebo group. There was no difference among the three treatment groups in the frequency of common adverse events (AEs) including infections. Four patients in each group experienced serious AEs (SAEs). 6 SAEs were due to infection, 3 SAEs were related to lupus, 3 were thromboembolic events, and one patient with positive anticardiolipin antibodies at baseline experienced a spontaneous abortion. One death occurred in the LAQ 1mg group (pan-lobar pneumonia & sepsis). There were no elevations of AST or ALT to above 3x ULN or bilirubin elevations above 2x ULN during the treatment period. Conclusions: In this exploratory study of patients with active Lupus Nephritis, LAQ 0.5 & 1mg in combination with SoC demonstrated an additive effect in improving renal function (as assessed by eGFR & proteinuria) compared to SoC alone. Although these signals are encouraging, this small phase IIa trial was not powered to definitively establish differences among the treatment groups. Both LAQ doses appeared to be well tolerated in this group of patients. A larger study of LAQ in combination with MMF and corticosteroids compared to SoC is planned in LN patients to confirm the safety and efficacy profile observed in this study. Disclosure of Interest: None Declared